2014
DOI: 10.2503/jjshs1.ch-082
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Pyridinedicarboxylic Acid Prolongs the Vase Life of Cut Flowers of Spray Carnations

Abstract: 2,4-Pyridinedicarboxylic acid (PDCA) is a structural analog of 2-oxoglutarate and has been shown to inhibit 2-oxoglutarate-dependent dioxygenases by competing with 2-oxoglutarate, and ethylene production in detached carnation flowers by competing with ascorbate on 1-aminocyclopropane-1-carboxylate (ACC) oxidase action. In the present study, the inhibition of ACC oxidase action by PDCA was confirmed with a recombinant enzyme produced in Escherichia coli from carnation DcACO1 cDNA. PDCA had various effects on et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 40 publications
3
33
3
Order By: Relevance
“…However, the mechanism of these diverse effects of PCA and PDCA analogs remain unknown. Previously, 2,4-PDCA was shown to inhibit the activity of prolyl-4-hydroxylase by acting as a structural analog of 2-oxoglutarate, the co-substrate of the enzyme (Vlad et al 2010), and that of ACC oxidase by acting as a possible structural analog of ascorbate, the co-substrate of the enzyme (Vlad et al 2010, Satoh et al 2014. Moreover, aconitase has been reported to be inactivated markedly by 2,6-PDCA, but not by 2,3-, 2,4-, and 2,5-PDCA (Murakami et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the mechanism of these diverse effects of PCA and PDCA analogs remain unknown. Previously, 2,4-PDCA was shown to inhibit the activity of prolyl-4-hydroxylase by acting as a structural analog of 2-oxoglutarate, the co-substrate of the enzyme (Vlad et al 2010), and that of ACC oxidase by acting as a possible structural analog of ascorbate, the co-substrate of the enzyme (Vlad et al 2010, Satoh et al 2014. Moreover, aconitase has been reported to be inactivated markedly by 2,6-PDCA, but not by 2,3-, 2,4-, and 2,5-PDCA (Murakami et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This action of 2,4-PDCA was later confirmed with spraytype carnation flowers, such as 'Light Pink Barbara (LPB)', which have a main stalk with several offshoots, each having one or two flowers at their tips (Satoh et al 2014). Then, Sugiyama and Satoh (2015) revealed that PDCA analogs, including 2,3-, 2,4-, 2,5-, 2,6-, 3,4-and 3,5-PDCA, could accelerate flower bud opening in addition to prolong the vase life of spray-type carnation flowers.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The effect of ethylene on flower senescence can be diminished by treating flowers with inhibitors of ethylene biosynthesis or action. Satoh et al (2014) have discussed several examples of such chemicals, which have been tested in trials or used practically in the flower industry. Treatment with these inhibitors prolongs the vase life of cut carnation flowers as well as other ethylene-sensitive ornamental flowers.…”
Section: Introductionmentioning
confidence: 99%